Biometrics of Pyramidalis Muscle and its Clinical Importance - Sushant Swaroop Das (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Pyramidalis is classified as a vestigial muscle which is frequently present. It is muscle of the anterior abdominal wall. It is thought to tense the linea alba. It has been used as a surgical landmark, source of muscle stem cells and in various surgical procedures. Aim: The aim of this study was to describe the morphometry and morphology of pyramidalis muscle in an adult Indian population and its correlation with the clinical significance. Materials and Methods: A cadaveric study on 25 formalin fixed cadavers (males-17, females-8) was conducted in context with prevalence, morphology and morphometry of pyramidalis muscle. Statistical analysis was done using the Chi-Square test and student’s t-test using SPSS version 23. Results: The pyramidalis muscle was present in 92% cases, usually bilaterally (72%) than unilaterally (20%) and more frequently in males (94.11%) than in females (87.5%). This study was conducted in Department of Anatomy, Maulana Azad Medical College, New Delhi, India from August 2014 to August 2016. Bilateral asymmetry was reported. The mean length of the muscle in males and females was 52.21±14.32 and 50.13±13.62mm on the right and 53.97±15.11 and 51.22±13.78mm on the left side. No significant gender predominance existed on the right and left-sided pyramidalis lengths. The mean width of the right-sided pyramidalis in males and females was 18.35±5.15 and 17.05±4.99mm and the left-sided was 17.8±4.80 and 16.21±4.23mm without gender dimorphism. The mean thickness of the right-sided pyramidalis in males and females was 4.91±1.33 and 4.53±1.29mm and the left-sided 4.33±1.28 and 4.38±1.27mm without gender differences. The mean pyramidalis-puboumbilical index was 35.15±4.38%, 36.01±4.97% in males and females respectively. No anatomical variations with regard to origin and insertion were seen. Conclusion: This study provides valuable information on pyramidalis muscle which may help in appropriate understanding of anatomy, functions and clinical significance of the muscle.